STRATEJIK MANAJEMEN PENGEMBANGAN KARIR WIDYAISWARA :Studi tentang Manajemen Pengembangan Karir Widyaiswara di Pusdiklat Regional Bandung Kementerian Dalam Neger - Bastra, Rochayati (2010)
This study titled Senior Lecturer in Strategic Management Career Development (Study of Career Development Management Senior Lecturer in the Environment Ministry of the Interior Regional Bandung) The background of the problem in the first) career development based on the results of performance evaluation that is attached to the performance of Senior Lecturer, 2) performance analysis of the delivery profile of abilities that sets each in accordance with the rank of Senior Lecturer, ideal positions and competencies that must be owned and 3) developing methods selected according to individual needs so that acceleration and accuracy of the achievement levels of functional position as Senior Lecturer keterhambatan not experience those problems and capabilities. Which became the focus of this research are: a. What about career program development Senior Lecturer in Environmental Education and Training Center Ministry of the Interior Regional Bandung today? b. Are the strengths and weaknesses in career development environment Senior Lecturer in the Interior Ministry, the Regional Training Center in Bandung today? c. How is Senior Lecturer career management about planning, implementaion, and evaluation? And d. How Career Development Models trainers? Qualitative approach used in this study, with interviews and observations used to extract data on Kemendagri Regional Training Center in Bandung. The result obtained are; program development of career widyaiswara cover the interest, profession and construction of profession. The weakness still felt is side recruitment which still place forward the bureaucracy side, and the strengtheen which have emerged that is governance autonomy give the opportunity to widyaiswara to manage the career of of level shall highest. Here in after improvement of profession integration with renumerasi the idealness. Interest by paying attention the required criteria, and in implementation of of the life cycle model still be altered so that can lessen the distortion power of bureaucracy. strategic Step recommendation which gone through; in the plan career have to pay attention the composition accomplishment of especial criterion and supporter criterion, career management adopt the models understudy, job giration and, coaching-counseling and develop the model by following the step; compilation of curriculum diklat functional, management diklat, stipulating of interest standard, compilation of guidance of formation, compilation of information system, and fasilitasi stipulating of profession ethics.